SPIRITUAL LEADERSHIP MANAGEMENT AND NURSING SERVICE QUALITY - sumantrie, pipin; Limbong, Martalina (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
ABSTRACT OBJECTIVE: Spiritual leadership has the potential to both directly and indirectly raise psychological patient satisfaction and work engagement. The most crucial element influencing patient satisfaction is the calibre of nursing care. Enhancing the quality of healthcare through a spiritual leadership style can boost employee retention and job satisfaction while achieving both internal and external goals. The purpose of this study was to ascertain how Spiritual Leadership Management affects and enhances the quality of nursing services.METHODOLOGY In this study, 68 nursing leaders from Adventist Hospital were selected at random using a mixed methods approach that included document studies and in-depth interviews with seven informants (n= 7 Heads of Departments and the Head of the Room). RESULTS: This study discovered a statistically significant relationship between the quality of nursing services and the use of spiritual leadership management. It had an impact on nursing service quality (p = 0.000), nursing leadership (0.01), spiritual leadership (0.00), and leadership factor (0.014) on Quality of Nursing Survive (p 0.05). Four themes emerged from the study, which demonstrated the impact of spiritual leadership on raising the calibre of nursing services: (1) The Role of Leaders in Organizations, (2) The Influence of Spiritual Leaders, (3) the leadership role in nursing, (4) Nursing service qualityCONCLUSION: The result indicates the importance of Spiritual leadership model implemented in caring behaviour in hospital services